Evaluation advanced lymph node dissection impact on long-term survival rate of gastric cancer patients - Dubinina, V. G.; Mashukov, A. A.; Zgura, A. N.; Bilenko, A. A.; Merlich, S. V.; Raziborsky, D. V.; Shilin, I. V. (Journal of Education, Health and Sport, 2015)
Dubinina V. G., Mashukov A. A., Zgura A. N., Bilenko A. A., Merlich S. V., Raziborsky D. V., Shilin I. V. Evaluation advanced lymph node dissection impact on long-term survival rate of gastric cancer patients. Journal of Education, Health and Sport. 2015;5(4):52-71. ISSN 2391-8306. DOI: 10.5281/zenodo.16594 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%284%29%3A52-71 https://pbn.nauka.gov.pl/works/553136 http://dx.doi.org/10.5281/zenodo.16594 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.01.2014. Revised 27.02.2015. Accepted: 15.03.2015. Evaluation advanced lymph node dissection impact on long-term survival rate of gastric cancer patients V. G. Dubinina1, A. A. Mashukov1, A. N. Zgura2, A. A. Bilenko1, S. V.Merlich2, D. V. Raziborsky2, I. V.Shilin2 Odessa National Medical University1, Odessa, Ukraine Odessa Regional Oncological Dispansery2, Odessa, Ukraine Abstract Over a period of 2007-2011 188 stomach cancer (SC) patients have been included in the research in abdominal oncosurgical department of Odessa regional oncological dispensary. It was retrospective, one-center, nonrandomized research. Volume of lymph node dissections differed by quantity of lymph nodes to be removed. All patients were divided into three groups. Patients with D1 or D1+ lymph node dissections have been performed, totally 90 patients are included in group of historical control. The main group includes 33 patients to whom D3 lymph node dissections is executed and, finally, control group – 65 patients dissected up to the D2 volume. In all cases so-called lymph node dissections for principal reasons have been executed. The multifactorial analysis of patients survival is implemented depending on a type of a lymph node dissections, a stage of the cancer, number of involved lymph nodes, involvement of the tumoral microcirculatory net (ly is carried out, v) signs of a perinevral invasion (Nev), availability of residual tumoral tissue (R), degree of a differentiation (G). Regardless of a disease stage, SC at 60% of patients, represented with initially hematologicaly disseminated disease. 40% of SC`s had no signs of intratumoral microcirculatory net involvement even in case of more than 15 regional lymph nodes are involved. In the absence of a SC perinevral invasion appeared to be the most precise predictive marker. The conclusion is made some brand new additional prognostic factors could play a crucial role in more accurate patients selection for expanded lymph node dissections. Keywords: stomach cancer, extended lymph node dissections.